Patent Foramen Ovale Device Closure in Cryptogenic Ischaemic Stroke: A Two Case Reports with Literature Review - Reza, AQM; Karim, Aparajita; Khan, Mahmood Hasan; Rahman, Kazi Atiqur; Joarder, Md Aliuzzaman; Rahman, Khondoker Mahbubur; Talukder, Shahab Uddin; Munwar, Shams; Ali, M Atahar; Ahmed, Tamzeed; et al. (Journal of National Institute of Neurosciences Bangladesh, 2022)
A patent foramen ovale (PFO) is highly prevalent in patients with strokes of unknown cause or cryptogenic strokes (CSs). It has been remain an unsolved question as to whether a PFO should be closed or not to prevent recurrent strokes in patients diagnosed with CS. A paradoxical embolism through a PFO is pointed as a leading cause of CS, especially in younger patients with low risk factors for stroke. It also remains an unsolved matter on type of anti-coagulation therapy, which would be better for patients with CS and a PFO. In addition, surgical and trans-cutaneous closure of a PFO has been proposed for the secondary prevention of stroke in patients with CS with PFO. Several randomized controlled trials have been conducted in recent years to test whether a PFO closure gives a significant benefit in the management of CS. Many investigators believed that a PFO was an incidental finding in patients with CS. However, meta-analyses and more recent specific trials have eliminated several confounding factors and possible biases and have also emphasized the use of a shunt closure over medical therapy in patients with CS. Therefore, these latest studies can possibly change the treatment paradigm in the near future. Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):90-99